Impacting Chatter and Stuck Dynamics of a Constrained Cantilever Beam - Luo, Albert C. J.; George, Richard (Journal of Vibration Testing and System Dynamics, 2026)
In this paper, the forced vibration of a cantilever beam at the free end constrained by two stops is studied. During vibration, the cantilever beam will impact and stuck with the two stops at the free end. Thus, the beam vibration will have different boundary conditions. It should be considered how many modes of vibrations can be used to describe the beam vibration. For impacting chatter and stuck at the free end of the beam, the constrained cantilever beam vibration is discussed in this paper, and analytical conditions for motion switching at the boundary of the cantilever beam are presented. From the analytical conditions, numerical simulations of periodic motions with motion switching are given for illustrations.